Effect of Triiodothyronine in Different Dosages on Growth and Survival Rate of Giant Gouramy (Osphronemus gouramy Lac.) - Herviani, I.; Junior, M. Zairin; Carman, Odang (Jurnal Akuakultur Indonesia, 2003)
This experiment was conducted to study the effect of giant gouramy larval immersion in triiodothyronine (T3) hormone solution on their growth and survival rate. One-day old larvae were treated with different concentrations of triiodothyronine (T3) i.e. 0; 0,001; 0,01; 0,1 and 1 ppm by immersion method for 24 hours. During eight weeks rearing period, larvae were fed to satiation with Tubifex three times daily. The media were aerated and changed 10-30% daily. At the end of experiment, there was no significant difference in yolk sac absorption between treated larvae and control. The highest dose of 1 ppm T3 resulted significant decreased in total length, average weight and survival rate of larvae. Key Word : Giant gouramy, Osphronemus gouramy, triiodothyronine, immersion dose, growth, survival rate.   ABSTRACT This experiment was conducted to study the effect of giant gouramy larval immersion in triiodothyronine (T3) hormone solution on their growth and survival rate. One-day old larvae were treated with different concentrations of triiodothyronine (T3) i.e. 0; 0,001; 0,01; 0,1 and 1 ppm by immersion method for 24 hours. During eight weeks rearing period, larvae were fed to satiation with Tubifex three times daily. The media were aerated and changed 10-30% daily. At the end of experiment, there was no significant difference in yolk sac absorption between treated larvae and control. The highest dose of 1 ppm T3 resulted significant decreased in total length, average weight and survival rate of larvae. Key Word : Giant gouramy, Osphronemus gouramy, triiodothyronine, immersion dose, growth, survival rate.